MANAJEMEN KOLABORASI DEWAN PERWAKILAN DAERAH (DPRD) KOTA BANDAR LAMPUNG DENGAN PEMERINTAH KOTA BANDAR LAMPUNG DALAM MEWUJUDKAN RUANG TERBUKA HIJAU - Ike Nurafni; Ari Darmastuti (Halu Oleo University, 2025)
The problem of Green Open Space (RTH) in Bandar Lampung City has not reached its optimal state, which is less than 20%. So that it causes instability in the city's health environment, affecting city regulations to be affected. The purpose of this article is to examine how cooperation in collaborative management of the Bandar Lampung City Government and the Bandar Lampung City DPRD in managing green open spaces in Bandar Lampung City. With the analysis of management theory in this study, the author uses George R. Terry's Theory, with stages of planning, organising, implementing and monitoring. This study uses a descriptive qualitative analysis methodology with data sources derived from previous literature studies or literature reviews, which are used as references in compiling this article. The results of the research findings show that there are still obstacles in the development space in the field of cooperation between the DPRD and the Environmental Service in terms of organising, implementing and supervising RTH. Program priorities and political obstacles are two things that prevent the program from achieving its goals. So, the principle of management collaboration that is shown is still not optimal, considering that the management process between institutions is still not strong enough to integrate, causing problems in strengthening the unification of the vision for organising green open spaces in Bandar Lampung City.